Kanwal urdu class 8 - "Fozia Ahsaan Faroqui" (Karachi : Oxford university press, 2023)
Urdu ka Guldasta is a series of colourful and stimulating textbooks for Classes Pre-Primary to 8. This bouquet has been gathered for young learners form the vast garden of Urdu literature. In this series, phonics and other methodologies that develop language skills effectively, as well as lessons based on imaginative new themes, enhance the children$1 (Bs proficiency. Each book in the series contains a Teaching Guide and a complete schedule of curricular objectives which will allow the teacher to understand the series and help to explain it to her/ his pupils.The textbooks for Pre-Primary and Primary classes have been revised and their salient features Addition of stories for picture comprehensions? Further exercises for reinforcement and practices? Demonstrates modern techniques of creative writing, comprehension and grammarStudent's Books and Teaching Guidess
Keywords: Urdu-text book; Oxford - text book